2020
DOI: 10.1049/iet-com.2019.0338
|View full text |Cite
|
Sign up to set email alerts
|

Symbol‐based multi‐layer iterative successive interference cancellation for faster‐than‐Nyquist signalling

Abstract: A symbol-based multi-layer iterative successive interference cancellation (MLISIC) algorithm is proposed to eliminate the inter-symbol interference (ISI) for faster-than-Nyquist (FTN) signaling. The computational complexity of the proposed MLISIC algorithm is much lower than most existing block-based estimation algorithms. By comparison with existing symbol-based algorithms, the proposed MLISIC algorithm has higher estimation accuracy. Furthermore, by means of utilizing more accurate symbols and elaborate leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The SSSgbK SE and MLISIC algorithms are not taken into account in this part because the IMLISIC algorithm has higher estimation accuracy than the former ones [25]. Some universal parameters adopted in the simulations are shown in Table 2, where and represent the length of block and cyclic prefix respectively.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SSSgbK SE and MLISIC algorithms are not taken into account in this part because the IMLISIC algorithm has higher estimation accuracy than the former ones [25]. Some universal parameters adopted in the simulations are shown in Table 2, where and represent the length of block and cyclic prefix respectively.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As shown in [25], the performance of the IMLISIC algorithm in moderate ISI cases is unsatisfactory although its performance degradation in mild cases can be neglected. We observed that its performance is quite bad after the first iteration, which means that desired performance cannot be achieved even with more iterations.…”
Section: Proposed Pre-equalized Inter-symbol Interference Cancellation a Pre-equalized Inter-symbol Interference Cancellationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, low complexity ISI algorithms based on successive interference cancellation can be found in [8–10], but these algorithms are applicable only in mild ISI cases. Besides, cyclic prefix (CP)‐based frequency‐domain equalisers for FTN signalling were evaluated over additive white Gaussian noise (AWGN) and frequency‐selective fading channels [11, 12].…”
Section: Introductionmentioning
confidence: 99%